(LACK OF )CONTEMPLATION: Implications for human relations from a people-centered perspective (Phenomenology, Humanities and Sciences, 2025)
This article aims to present and analyze the concept of contemplation and the effects of what we call lack of contemplation, as a basis for prejudice and other non-contemplative forms of human relationships. Based on the theoretical-methodological perspectives of the Person-Centered Approach (PCA), in this study we explore the manifestations of the contemplative phenomenon and its implications for understanding the intrinsic and extrinsic human organism subjectivities. Through a literature review, we present what we call contemplation, propose an expansion of PCA facilitating attitudes, and then examine how lack of contemplation manifests itself in various spheres of everyday life, such as intercultural relations, power relations and social structures, presenting eight markers of intersectionalities that relate to resistances against today's recognized lacks of contemplation. Finally, we discuss the importance of openness to experience, based on an actively contemplative posture that promotes more unconditional, empathetic and authentic relationships between individuals. By addressing this theme, the article seeks to contribute to the advancement of the phenomenological understanding of human interactions and to the development of therapeutic, educational and social approaches that are more centered on not only the individual, but also the collective dimensions of people.
Keywords: contemplation; lack of contemplation; person-centered approach; intersectionality; human relations